2021
DOI: 10.1371/journal.pone.0246283
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices related to COVID-19 pandemic among adult population in Sidama Regional State, Southern Ethiopia: A community based cross-sectional study

Abstract: Introduction COVID-19 incidence is increasing and different measures have been adopted to control the spread of the pandemic in Ethiopia. Among these measures, enhancing the knowledge, positive attitudes, and proper practices of prevention measures about the disease is a basic strategy to control it. However, community compliance to control measures is largely dependent on their knowledge, attitudes, and practices (KAP) towards COVID-19. Objective To assess the current level of KAP towards COVID-19 pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
44
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 6 publications
24
44
12
Order By: Relevance
“…The level of good knowledge in this study is comparable to a study done in Amhara region where 279 (70%) had demonstrated good knowledge and relatively higher when compared to studies conducted among residents of Dessie and Kombolcha city administrations where 54.11% had inadequate knowledge ( 16), Tigray region where 42.9% of respondents were knowledgeable (17), Sidama region where 43.9% of the study participants had good knowledge (18) and Addis Abeba where only 37.2% had good knowledge (19). The level of poor knowledge is much lower than a study conducted in Addis Zemen Hospital where the prevalence of poor knowledge was 33.9% (20).…”
Section: Discussionsupporting
confidence: 77%
“…The level of good knowledge in this study is comparable to a study done in Amhara region where 279 (70%) had demonstrated good knowledge and relatively higher when compared to studies conducted among residents of Dessie and Kombolcha city administrations where 54.11% had inadequate knowledge ( 16), Tigray region where 42.9% of respondents were knowledgeable (17), Sidama region where 43.9% of the study participants had good knowledge (18) and Addis Abeba where only 37.2% had good knowledge (19). The level of poor knowledge is much lower than a study conducted in Addis Zemen Hospital where the prevalence of poor knowledge was 33.9% (20).…”
Section: Discussionsupporting
confidence: 77%
“…The level of education was also reported as a significant factor in the study conducted in Sidama and Tigrai regions of Ethiopia. 11 12 Moreover, studies done in South West Ethiopia, 13 Tigrai 12 and Palestine 14 added that level of knowledge is a significant factor of COVID-19 prevention. This indicated that level of awareness is important to prevent the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The reason might be since the current study was conducted after most of the population obtained information about the disease in several ways (Gebretsadik et al, 2021). Gebretsadik et al (2021) and Yoseph et al (2021) also stated that it might be due to the study participants getting access to the internet service, which helped them find information about the disease from several sources. Other studies showed that the excellent knowledge of COVID-19 might be due to the study respondents live in urban residence with higher education degree (Gao et al, 2020;Mohamed et al, 2021).…”
Section: Knowledge Toward Covid-19 Preventionmentioning
confidence: 99%
“…Many researchers reported that public attitude toward COVID-19 was optimistic (Azlan et al, 2020;Gao et al, 2020;Kartheek et al, 2020;Okello et al, 2020;Yoseph et al, 2021). This is possible because the belief can pass this situation and win against the disease by supporting lockdown decision and following restrictive policies (Kartheek et al, 2020).…”
Section: Attitude Toward Covid-19 Preventionmentioning
confidence: 99%
See 1 more Smart Citation